Health insurance enrolment in the Upper West Region of Ghana: Does food security matter?. (18th July 2019) - Antabe, Roger; Atuoye, Kilian Nasung; Sano, Yujiro; Kuuire, Vincent Zubedaar; Galaa, Sylvester Zachariah; Luginaah, Isaac
Summary: Toward achieving universal health coverage, Ghana's national health insurance has been acclaimed as a pro‐poor scheme, yet been criticized for leaving the poor behind. Arising from this is how poverty has been operationalized and how poor people are targeted for enrolment into the scheme. We examine the role of food insecurity (not currently considered) as a multidimensional vulnerability concept on enrolment into Ghana's health insurance using binary logistics regression on cross‐sectional survey of household heads (n = 1438) in the Upper West Region of Ghana. Our analyses show that heads of severely food‐insecure households were significantly less likely to enroll in national health insurance scheme (NHIS) relative to households who reported being food‐secure (OR = 0.36, P < .05). We also found education, occupation, and religion as significant predictors of health insurance enrolment. Based on our findings, it is crucial to incorporate food security status in the identification of vulnerable people for free enrolment in Ghana's health insurance.